Changes in photoperiod during the dry period impact colostrum production in Holstein and Jersey cows - K.J. Alward; A.J. Duncan; A.D. Ealy; G.E. Dahl; C.S. Petersson-Wolfe; R.R. Cockrum (Journal of Dairy Science)
ABSTRACT: Multiparous Holstein cows exposed to short-day photoperiod (SDPP) of 8 h of light per day during their dry period produced up to 3.2 kg more milk per day compared with cows exposed to long-day photoperiod (LDPP) of 16 h of light per day; it is unknown if a similar response would be observed for Jersey cow milk production. The objective of this study was to determine the effect of photoperiod during the dry period on subsequent colostrum and milk production in Holstein and Jersey cattle. Holstein and Jersey cows (n = 33) were dried off 60 d before their due date and randomly assigned to SDPP (Holstein, n = 9; Jersey, n = 8) or LDPP (Holstein, n = 8; Jersey, n = 8) until calving. Cows were weighed at the time of enrollment (d 0) and were housed in an enclosed barn at 20°C and exposed to 250 to 450 lx during periods of light and <10 lx during periods of darkness. At calving, colostrum volume was weighed and tested for relative protein concentration with a Brix refractometer and a sample was collected for component analysis (fat, protein, lactose, SNF) via infrared spectroscopy, as well as IgA, IgG, IgG1, IgM, lactoferrin, and SCS analysis. After calving, cows were returned to the freestall barn and exposed to ambient photoperiod and temperature. Milk production data were collected for 15 wk postcalving. Data were analyzed using PROC MIXED in SAS (SAS 9.4; SAS Institute Inc., Cary, NC) with treatment, breed, and d 0 weight as fixed effects. PROC MIXED with repeated measures was used to evaluate the relationship of day length and breed with mature milk volume, fat, and protein production. Random effects included replicate, lactation number, genetic inbreeding percentage, previous lactation mature equivalent 305-d protein production, and calf sex. For colostrum, Brix score, colostral protein, fat, IgA, and IgM were increased in Jersey cows compared with Holstein cows. Total colostrum weight, SNF, lactose, lactoferrin, IgG, IgG1, and SCS did not differ by breed or treatment. Postcalving, ECM production was increased in Holstein cows compared with Jersey cows but unaffected by photoperiod treatment. Conversely, milk protein percentage was increased for Jersey cows relative to Holstein cows but was unaffected by photoperiod treatment. Milk fat increased in LDPP Holstein cows compared with SDPP Jersey cows during the first week of lactation, which is likely due to the transition from colostrum to mature milk production. Overall, photoperiod did not affect colostrum production, but differences by breed were detected. Photoperiod during the dry period did not affect mature milk production or protein, but milk fat percentage was affected by photoperiod × breed. Therefore, altered lighting during the dry period does not unfavorably affect colostrum or milk production in Jersey or Holstein cows.